The Condition and Prospects of Innovativeness of Enterprises in Peripheral Regions of North-Eastern Poland - Małgorzata JUCHNIEWICZ; Zbigniew NASALSKI (Communications of International Proceedings, 2022)
The aim of the research was to determine the state and conditions for the development of innovation in enterprises operating in the peripheral regions of north-eastern Poland (in the poviats: Bartoszyce, Braniewo, Ketrzyn and Lidzbark Warminski). The innovativeness of enterprises operating in the peripheral regions of north-eastern Poland is at a low level. On the other hand, innovation may be an important factor in increasing the competitiveness of enterprises and its development should also be pursued in regions with low economic potential. It should be emphasized that the surveyed entrepreneurs were aware of the importance of innovation in the process of competing. The most important obstacles in conducting innovative activity were considered by the surveyed entrepreneurs, first of all, of high costs and limited access to funds, as well as too high market risk in peripheral areas. Activities aimed at the development of innovative activities in the peripheral regions of north-eastern Poland should include modification of individual innovation strategies, increased involvement in institutional relations aimed at searching for and implementing innovative strategies, greater involvement in cooperation with the business environment, greater attention to complementarity in activities aimed at customer retention and innovation. The second important pillar of support for the development of innovative potentials in peripheral areas should be the activities of local governments, which should focus primarily on: creating a climate for innovation and optimizing formal and legal procedures.
Keywords: innovation; innovation policy; peripheral regions; regional development